Qing-Xin-Jie-Yu Granule for patients with stable coronary artery disease (QUEST Trial): A multicenter, double-blinded, randomized trial. (December 2019) - Li, Jingen; Gao, Zhuye; Zhang, Lijing; Li, Shengyao; Yang, Qiaoning; Shang, Qinghua; Gao, Xiang; Qu, Hua; Gao, Jie; Shi, Lixiao; Liu, Yue; Du, Jianpeng; et al.
Highlights: Patients with stable coronary artery disease (SCAD) remain at high risk of cardiovascular event. Qing-Xin-Jie-Yu Granule has been shown to alleviate symptom in patients with SCAD. Qing-Xin-Jie-Yu Granule might be associated with reduced cardiovascular events. Abstract: Background and aim: Despite optimal secondary preventive treatment, patients with stable coronary artery disease (SCAD) remain at high risk of cardiovascular events. This multicenter, double-blinded, randomized trial sought to determine whether the addition of Qing-Xin-Jie-Yu Granule (QXJYG), a traditional Chinese medicine prescription, to standard therapy would further reduce risk of cardiovascular events in patients with SCAD. Methods: A total of 1500 patients with documented SCAD were randomly assigned in a 1:1 ratio to QXJYG or placebo for 6 months, and followed up for another 6 months. The primary outcome was a composite of cardiovascular death, nonfatal myocardial infarction (MI) and coronary revascularization. Near the end of the trial, but before unblinding, a commonly used composite 'hard' endpoint composed of cardiovascular death, nonfatal myocardial infarction and ischemic stroke was additionally analyzed. Results: During a median follow-up of 12 months, no significant difference of the primary outcome between the two groups was observed (1.59% vs. 1.62%; hazard ratio, 0.41; 95% CI, 0.13–1.28). However, absolute risk of the composite 'hard' endpoint was reduced by 0.99% (0.31% vs. 1.30%; hazard ratio, 0.06; 95%CI, 0.01 to 0.53). No difference of adverse events between the two groups was observed. Conclusion: In patients with SCAD, the addition of QXJYG to standard therapy was associated with reduced risk of nonfatal MI and the composite 'hard' endpoint of cardiovascular death, nonfatal MI and stroke. (http://www.chictr.org.cn/showproj.aspx?proj=5200, ChiCTR-TRC-13004370).